THE REALISTIC DEPICTION OF POVERTY AND URBAN LIFE - Eldorbek Erkin og’li Khamitov,; Markabaeva Mexriban Keulimjayevna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This  paper  examines  how  literature  realistically  portrays  poverty  and  life  in urban areas. Realist writers focus on ordinary people and their daily struggles, showing how  poverty  influences  every  part  of  life,  including  work,  family,  education,  and health. Cities are described in detail, with crowded streets, poor living conditions, and the difficulties people face in urban environments. The  study  shows  that  characters  in  realist  fiction  often  experience  financial problems,  unemployment,  and social inequality. Through their  experiences, writers reveal  how  poverty  limits  opportunities,  affects  personal  relationships,  and  creates social challenges. Realist authors also highlight the differences between social classes, showing the gap between the rich and the poor and demonstrating how society can be unfair and difficult to navigate. Urban life is portrayed as both a place of opportunity and a source of struggle. Writers describe neighborhoods, streets, workplaces, and social interactions to make the setting realistic and vivid. Poverty is also connected to moral issues, such as crime, corruption, and social responsibility, which adds depth to the stories. In conclusion, realist fiction uses the depiction of poverty and urban life to show real social problems. It allows readers to understand human struggles and the effects of  inequality.  By  presenting  life  in  cities  and  the  hardships  of  poor  people,  realist writers  encourage  empathy  and  reflection,  making  these  works  valuable  for understanding society.